ANXIETY SENSITIVITY BIAS AND COLLECTIVE ACTION PARADOX IN EPIDEMIC PREVENTION AND RESPONSE IN WESTERN COUNTRIES — AN ANALYSIS BASED ON INCOMPLETE INFORMATION LEARNING MODEL - Qiu, Fei; Xu, Lan (The international journal of neuropsychopharmacology, 2022)
Abstract Background In order to cope with the public health crisis caused by the 2019 coronavirus disease epidemic, a prominent feature of Western society is that residents are unwilling to take the initiative to wear masks for protection. The cultural tradition and social psychological explanation of this phenomenon is that most people are unwilling to wear masks because the masks in western society have the symbol of uncleanness and weakness. This explanation of cultural tradition and social psychology makes some sense. However, social behavior is also influenced by the government. Why don't Western governments adopt mandatory policies to correct the negative impact of current social psychology from the perspective of ensuring public safety? One popular explanation is that western countries have politicized the 2019 coronavirus epidemic, so they are unwilling to take correct measures to deal with the epidemic. But this irrational explanation is incredible. The managerial man hypothesis is only an ideal abstract concept, but individuals in society may occasionally make irrational behavior because of psychological resistance. But in general, the behavior of institutions and governments is more rational than that of individuals. It is incredible that many Western governments violate the principle of rationality on such a large scale. At the same time, in the face of the COVID-19, a global health emergency, the anxiety sensitivity of people in western countries is also worth paying attention to. Subjects and Methods By constructing a learning model under the condition of incomplete information, this paper explains how residents and the government obtain information, and how social values determine the optimal choice of the government in coordinating social collective action. This paper also uses anxiety sensitivity Index-3, which is an evaluation tool developed by Taylor and others based on previous studies. It covers three specific dimensions of anxiety sensitivity construct, involving attention to individual cognition, society and body. Six items in each of the three subscales were scored by Likert level 5 (0 = very few, 1 = less, 2 = medium, 3 = more, 4 = very many), and the total score was used to represent the individual's anxiety sensitivity level [15]. It can also analyze three special factors: social attention, cognitive attention and physical attention. When researchers want to use special factors such as social attention, cognitive attention and physical attention to predict external variables, they can independently explain the prediction results without considering the influence of public factors. Results Under the Bayesian information acquisition rule, when the whole society does not pay attention to cooperative behavior, the seemingly irrational behavior of Western governments reflects the trap of “white lie” and “rational inaction” to deal with the impact of social systemic risk. Results: Our results showed that although anxiety was positively correlated with government media information, it was not statistically significant (P > 0.05). Among the psychological anxiety of the masses, debilitating anxiety dominated, and the results were statistically significant (P < 0.01). This means that debilitating anxiety can be used as an indicator to measure the level of people's anxiety. Our results show that environmental anxiety is negatively correlated with information. The Pearson correlation in the high anxiety group was significantly higher than that in the low anxiety group. This shows that students with less media influence are more likely to be anxious than those with more media influence. Conclusion Social values affect social psychology, and social psychology affects the effect of government governance. The values and social psychology that bring long-term success to society may also lead to disaster management to deal with sudden crises. The strong individualistic values in western society are conducive to innovative activities in the period of social stability, but not conducive to highly coordinated social collective action in the period of social crisis. In order to avoid these governance traps, in the long run, we can improve the level of trust and cooperation in society by strengthening social capital; In the short term, the prejudice of social psychology against science and technology and scientific researchers must be eliminated. It has better fitting in the Chinese version of anxiety sensitivity Index-3, which is also of great significance for accurately understanding the structure of anxiety sensitivity. Acknowledgements This study was supported by the Youth Foundation for Humanities and Social Sciences Research of the Ministry of Education, China (Grant No.18YJC790131), Zhejiang Public Welfare Technology Application Research Funding Project, China (Grant No. LGF22G010002) and Applied Economics Base Project of Zhejiang Wanli University, China (Grant No.SZ10000018).